Private retirement savings in Australia: Current policy initiatives and gender equity implications - Jefferson, Therese (National Institute of Labour Studies, 2012)
This article assesses the implications for gender equity of three recent policy initiatives on superannuation in Australia: (i) government co-contributions for low-income earners; (ii) an increase in compulsory superannuation contributions from 9 to 12 per cent; and (iii) the pending introduction of ‘MySuper’ accounts, specifically designed for those who do not take an active interest in their superannuation accumulation. Implications for gendered patterns of superannuation coverage and superannuation accumulations are considered. The conclusion is that while the first measure may have some beneficial outcomes in terms of gendered patterns of accumulation, none of the three measures appears to deal with issues associated with gendered patterns of access to occupational superannuation.